Simplifying complexities of nonparallel abutments - Sheen J Arora; Aman Arora; Divya Malik (Wolters Kluwer Medknow Publications, 2017)
The success of the prosthetic rehabilitation in a long-span fixed partial denture (FPD) requires adequate restoration of its function, periodontal health, and esthetics. This case report describes various treatment options to overcome stresses produced in a long-span FPD with tilted molar.